Fusing fact and fiction: biography and autobiography in the novels of Virginia Woolf - White, Joshua Craig (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2016)
Virginia Woolf was noted for a preoccupation with the genre of life-writing throughout her career. Her aims when it came to reshaping the nature of biographical and autobiographical literature were numerous. She veered away from the aggrandising and patriarchal methods with which Victorian biographers tended to depict their subjects. She increased the focus on women in life-writing, examining and subverting traditionally prescribed gender roles prevalent in both her society and the literature that reflected it, and advocating a balance between male and female patterns of thinking. She also devised a method of incorporating both basic biographical fact and aspects of fiction into life-writing in order to approach a more truthful depiction of a subject's personality or character. This method is linked to the aforementioned balance of gendered thought patterns, since Woolf often aligns factuality with male thinking and the contrasting qualities of fiction, such as intuition, ambivalence and perspicacity, with female thinking. This thesis examines three novels which demonstrate Woolf's constant preoccupation with combining fact and fiction in order to capture the essence of personality. In her debut novel, The Voyage Out, she presents Rachel Vinrace, who must achieve a balance of male-oriented fact with female-oriented insight in order to fashion a sufficient identity for herself and to identify others in a selective and judicious manner, thus being simultaneously autobiographical and biographical. In Orlando, Woolf explicitly subverts the traditional Victorian biography by depicting Vita Sackville-West as a man who transforms into a woman and remains living for over 400 years. In presenting such a character, Woolf posits that personality consists of and is influenced by myriad aspects of a person's life that cannot be documented in the restrictive manner employed by Victorian biographers. Orlando's essence being obfuscated by manifold "selves" attests to Woolf problematizing attempts to attain such an essence. The same challenge is particularly important in her autobiographical novel, To the Lighthouse, in which she transposes the traumas of her own life into a fictitious narrative in order to achieve catharsis for her and her readers, and to present the difficulty in capturing the essence of character. The conclusion that Woolf eventually posits is that personality cannot be reduced to an essence, but rather that it consists of idiosyncrasies that are various, intertwining, and capricious.
Keywords: Uncatalogued